Telemedical management in patients waiting for transcatheter aortic valve implantation: the ResKriVer-TAVI study design - Isabel Mattig; Isabel Mattig; Isabel Mattig; Isabel Mattig; Kerstin Koehler; Kerstin Koehler; Kerstin Koehler; Gina Barzen; Gina Barzen; Meike Hiddemann; Meike Hiddemann; Meike Hiddemann; et al. (Frontiers in Cardiovascular Medicine, 2024)
AimsThe majority of patients with severe aortic stenosis (AS) planned for transcatheter aortic valve implantation (TAVI) are elective outpatients. During the COVID-19 pandemic, the time between the heart team’s decision and TAVI increased due to limited healthcare resources. We therefore implemented telemedical approaches to identify AS patients at risk for clinical deterioration during the waiting time. The purpose of the prospective, randomized, controlled ResKriVer-TAVI study (DRKS00027842) is to investigate whether a digital concept of telemedical interventional management (TIM) in AS patients waiting for TAVI improves the clinical outcomes. In the present article, we report the study protocol of the ResKriVer-TAVI trial.MethodsResKriVer-TAVI will enroll AS patients planned for elective TAVI. Randomization to the TIM group or standard care will be made on the day of the heart team’s decision. TIM will include a daily assessment of weight, blood pressure, a 2-channel electrocardiogram, peripheral capillary oxygen saturation, and a self-rated health status until admission for TAVI. TIM will allow optimization of medical therapy or an earlier admission for TAVI if needed. Standard care will not include any additional support for patients with AS. All patients of the TIM group will receive a rule-based TIM including standard operating procedures when a patient is crossing prespecified values of a vital sign.ResultsThe primary endpoint consists of days lost due to cardiovascular hospitalization and death of any cause within 180 days after the heart team’s decision. Major secondary endpoints include all-cause mortality within 365 days, the number of telemedical interventions, and adherence to TIM. Follow-up visits will be conducted at admission for TAVI as well as 6 and 12 months after the heart team’s decision.ConclusionsResKriVer-TAVI will be the first randomized, controlled trial investigating a telemedical approach before TAVI in patients with AS. We hypothesize that primary and secondary endpoints of AS patients with TIM will be superior to standard care. The study will serve to establish TIM in the clinical routine and to increase the resilience of TAVI centers in situations with limited healthcare resources.